Empirical evaluation of a model of antecedents of customer loyalty in the pharmaceutical retail sector - Godinho, Luiz Antônio de Carvalho; Pereira, Gisele de Araújo; Gosling, Marlusa (Revista de Administração da UFSM, 2018)
Relationship marketing has long been presented as a possibility for companies to differentiate themselves in their markets, and some concepts have been widely studied in this direction, especially loyalty. In this context, this work aimed to validate a model that shows the relationship between some antecedent variables to loyalty in the context of a convenience market - the drugstore market, seeking to understand how the customer perceived value, satisfaction, trust and loyalty are related. To this end, a descriptive conclusive research applied to a sample of 602 respondents was conducted and 3 focus groups were also conducted as a reference for defining the scales. To analyze the model the technique of structural equation modeling with Partial Least Squares (PLS) was used. Participants were clients of three stores from one of the largest pharmaceutical companies in a capital of southeastern Brazil. The results indicated that at the surveyed stores, perceived value and trust had a positive and significant impact on loyalty. In addition, satisfaction had a mediating role in relation to perceived value and loyalty, but it was not considered a good direct antecedent of loyalty, since it interfered in the significance between trust and loyalty. Trust also had a mediating effect between satisfaction and loyalty, confirming the findings of supportive literature. Relationship marketing has long been presented as a possibility for companies to differentiate themselves in their markets, and some concepts have been widely studied in this direction, especially loyalty. In this context, this work aimed to validate a model that shows the relationship between some antecedent variables to loyalty in the context of a convenience market - the drugstore market, seeking to understand how the customer perceived value, satisfaction, trust and loyalty are related. To this end, a descriptive conclusive research applied to a sample of 602 respondents was conducted and 3 focus groups were also conducted as a reference for defining the scales. To analyze the model the technique of structural equation modeling with Partial Least Squares (PLS) was used. Participants were clients of three stores from one of the largest pharmaceutical companies in a capital of southeastern Brazil. The results indicated that at the surveyed stores, perceived value and trust had a positive and significant impact on loyalty. In addition, satisfaction had a mediating role in relation to perceived value and loyalty, but it was not considered a good direct antecedent of loyalty, since it interfered in the significance between trust and loyalty. Trust also had a mediating effect between satisfaction and loyalty, confirming the findings of supportive literature.